Tunjuk Ajar Melayu dalam Syair Karya Tenas Effendi sebagai Basis Pendidikan Karakter - Alber, Alber (GERAM: Gerakan Aktif Menulis, 2017)
This paper aims to describe the teaching of Malay in Tenas Effendy’s Poem as a base of character education. Poem contains various contents, mainly meaningful stories and a variety of religious advice that could be used as a reference in daily life. Therefore, indirectly, poetry is a base for character education not only because of the values inside, but also because of the strategies for the local wisdom preservation. The theory used Kemendiknas (2010), Effendy (2013), dan Syafri (2014). This paper is descriptive-analytic with descriptive qualitative method. The data sources are Tunjuk Ajar Melayu books from Tenas Effendy (2013). Based on the analysis, it can be indicated that the Teaching of Malay from Tenas Effendy Tenas Poem contributed to character education. The points that contributed to character education are religious value, social care, discipline, honesty, independence, responsibility, love peace, tolerance, caring environment, friendly/communicative, democratic, hard work, and curiosity.